Improving Secondary School Students’ Vocabulary Mastery through Scattergories Game - Kordja, Baharuddin (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2023)
This study aims to determine whether the scattergories game significantly enhances Makassar junior high school students' vocabulary mastery. The researcher employed a pre-experimental design with a pre- and post-test for a single group. The experimental design included a group that was given a pretest, then exposed to a treatment, and then given a posttest. This study's participants were eighth-grade students at SMPN 27 Makassar. The class that comprised the study's sample was determined using cluster random sampling. The results indicated that the average score on the post-test was higher than the average score on the pretest; the average score on the post-test was (84.27), while the average score on the pretest was (32.20). The test score for the hypothesis is less than 0.05, specifically 0.00 0.05. Therefore, the null hypothesis (H0) is refuted, and the alternative hypothesis (H1) is accepted. Based on the analysis, it can be concluded that implementing the scattergories game to the eighth-grade students at SMPN 27 Makassar substantially improved their English vocabulary knowledge.